Three New Species of Cnemaspis (Sauria: Gekkonidae) from Sarawak, East Malaysia, Borneo - Nashriq, Izneil; Davis, Hayden R.; Bauer, Aaron M.; Das, Indraneil (Zootaxa, 2022)
Three new species of Cnemaspis are described from karst regions of Sarawak, Malaysia, on the island of Borneo. These are Cnemaspis matahari sp. nov. and C. sirehensis sp. nov. from limestone hills located in the Serian Division of western Sarawak, and C. lagang sp. nov. from Gunung Mulu, Miri Division, in northern Sarawak. All can be distinguished from congeners using mitochondrial DNA as well as an enlarged metatarsal scales on the first toe. Individually, each species can be diagnosed by differences in subcaudal scale morphology: Cnemaspis lagang sp. nov. lacks enlarged subcaudals; Cnemaspis matahari sp. nov. has keeled subcaudals bearing an enlarged median row of smooth scales; and Cnemaspis sirehensis sp. nov. has an enlarged median row of weakly keeled scales. The discovery of these species suggests that additional unrecognized species may exist within the genus on Borneo, especially in association with karst formations. High endemism and species diversity notwithstanding, these karst formations are under severe pressure from limestone extraction and deforestation.